Influence of Feeding Weaned Piglets with Laminaria digitata on the Quality and Nutritional Value of Meat - Ribeiro, David Miguel (2022)
Laminaria digitata is a novel feedstuff that can be used in pig diets to replace conventional feedstuffs. However, its resilient cell wall can prevent the monogastric digestive system from accessing intracellular nutrients. Carbohydrate-active enzyme (CAZyme) supplementation is a putative solution for this problem, degrading the cell wall during digestion. The objective of this work was to evaluate the effect of 10% L. digitata feed inclusion and CAZyme supplementation on the meat quality and nutritional value of weaned piglets. Forty weaned piglets were randomly allocated to four experimental groups (n = 10): control, LA (10% L. digitata, replacing the control diet), LAR (LA + CAZyme (0.005% Rovabio® Excel AP)) and LAL (LA + CAZyme (0.01% alginate lyase)) and the trial lasted for two weeks. The diets had no effect on any zootechnical parameters measured (p > 0.05) and meat quality traits, except for the pH measured 24 h post-mortem, which was higher in LAL compared to LA (p = 0.016). Piglets fed with seaweed had a significantly lower n-6/n-3 PUFA ratio compared to control, to which the higher accumulation of C20:5n-3 (p = 0.001) and C18:4n-3 (p < 0.0001) contributed. In addition, meat of seaweed-fed piglets was enriched with bromine (Br, p < 0.001) and iodine (I, p < 0.001) and depicted a higher oxidative stability. This study demonstrates that the nutritional value of piglets’ meat could be improved by the dietary incorporation of L. digitata, regardless of CAZyme supplementation, without negatively affecting growth performance in the post-weaning stage